2017
DOI: 10.1080/15476286.2017.1302640
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing reveals circular substrates for an archaeal RNA ligase

Abstract: It is only recently that the abundant presence of circular RNAs (circRNAs) in all kingdoms of Life, including the hyperthermophilic archaeon Pyrococcus abyssi, has emerged. This led us to investigate the physiologic significance of a previously observed weak intramolecular ligation activity of Pab1020 RNA ligase. Here we demonstrate that this enzyme, despite sharing significant sequence similarity with DNA ligases, is indeed an RNA-specific polynucleotide ligase efficiently acting on physiologically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…70,71 An additional way to protect RNA termini against exonucleolytic activity is the ligation of available 5ʹ and 3ʹ termini, resulting in the formation of circular RNA species. 13,72,73 The described circular T. tenax SRP RNA exemplifies this case (Fig. 2B).…”
Section: ʹ Rna Termini and Possible Capping Mechanismsmentioning
confidence: 56%
See 1 more Smart Citation
“…70,71 An additional way to protect RNA termini against exonucleolytic activity is the ligation of available 5ʹ and 3ʹ termini, resulting in the formation of circular RNA species. 13,72,73 The described circular T. tenax SRP RNA exemplifies this case (Fig. 2B).…”
Section: ʹ Rna Termini and Possible Capping Mechanismsmentioning
confidence: 56%
“…The translation initiation factor a/eIF2 can bind mRNAs with 5ʹppp ends (but not RNAs with 5ʹp or 5ʹpp ends) to provide protection from Sso‐aCPSF2 degradation, and in vivo experiments showed that the overproduction of a/eIF2(γ) increases the stability of different mRNAs . An additional way to protect RNA termini against exonucleolytic activity is the ligation of available 5ʹ and 3ʹ termini, resulting in the formation of circular RNA species . The described circular T. tenax SRP RNA exemplifies this case (Fig.…”
Section: ʹ Rna Termini and Possible Capping Mechanismsmentioning
confidence: 95%
“…Circularization of RNA is widespread in archaea ( Danan et al, 2012 ) and P. furiosus appears to be particularly prone to RNA circularization, e.g., with abundant circularization of box C/D RNAs ( Starostina et al, 2004 ). Recently, an RNA ligase that ligates 5´-P and 3´-OH ends was characterized from Pyrococcus abyssi (the Pab 1,020 RNA ligase) and proposed to circularize many different cellular RNAs ( Becker et al, 2017 ). The excision of H98 in P. furiosus curiously resembles a step in rRNA processing in chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the role and mechanism of circRNAs in tumor progression are still not well identified [ 15 ]. Although circRNAs have been discovered for decades, the significance of circRNAs is recognized with the developing of high-throughput RNA-sequencing (RNA-Seq) and bioinformatics analysis [ 16 , 17 ]. Emerging evidences have illustrated that circRNAs play important role in multiple physiological and pathological functions, involving cardiovascular system disease, nervous system disease and series of tumors [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%